2010
DOI: 10.1371/journal.pone.0008931
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-α in the Bed Nucleus of the Stria Terminalis Regulates Social Affiliation in Male Prairie Voles (Microtus ochrogaster)

Abstract: Estrogen receptor alpha (ERα) typically masculinizes male behavior, while low levels of ERα in the medial amygdala (MeA) and the bed nucleus of the stria terminalis (BST) are associated with high levels of male prosocial behavior. In the males of the highly social prairie vole (Microtus ochrogaster), increasing ERα in the MeA inhibited the expression of spontaneous alloparental behavior and produced a preference for novel females. To test for the effects of increased ERα in the BST, a viral vector was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 42 publications
(58 reference statements)
6
44
0
1
Order By: Relevance
“…In socially monogamous prairie and pine ( M. pinetorum ) voles, ERα expression in the MEApd and BSTpm is sexually dimorphic (Cushing et al 2004, Cushing and Wynne-Edwards 2006) and low levels are “necessary” for the expression of prosocial behavior in males (Cushing et al 2008, Lei et al 2010). Males of these species also display relatively longer EL and PEI compared to the closely-related polygynous montane ( M. montanus ) and meadow ( M. pennsylvanicus ) voles (Dewsbury, 1973; 1976; Gray and Dewsbury, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In socially monogamous prairie and pine ( M. pinetorum ) voles, ERα expression in the MEApd and BSTpm is sexually dimorphic (Cushing et al 2004, Cushing and Wynne-Edwards 2006) and low levels are “necessary” for the expression of prosocial behavior in males (Cushing et al 2008, Lei et al 2010). Males of these species also display relatively longer EL and PEI compared to the closely-related polygynous montane ( M. montanus ) and meadow ( M. pennsylvanicus ) voles (Dewsbury, 1973; 1976; Gray and Dewsbury, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of polygynous and monogamous species shows this to be a general pattern (Cushing and Wynne-Edwards, 2006; Wu et al, 2010). Additionally, increasing ERα expression in the MEApd or BSTpm of IL males significantly reduced prosocial behavior (Cushing et al, 2008; Lei et al, 2010), whereas down-regulation of hypothalamic ERα expression reduces sexual activity in female rats (Spiteri et al, 2012). A role for TH neurons in the MEApd and BSTpm in sociosexual organization has also been inferred, as polygynous species possess fewer TH neurons in these regions than monogamous species, which project primarily to the MPOA and are activated by sociosexual stimuli (Cavanaugh and Lonstein, 2010; Northcutt and Lonstein, 2011; Northcutt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of ER␣ differs across social and nonsocial species and plays a significant role in regulating speciesspecific sociality (93). Increased ER␣ in the pBNST, for example, reduces male prosocial behaviors (13,94). The male prairie vole pBNST is also richly populated with TH-ir cells, some of which are colocalized with ER␣.…”
Section: Discussionmentioning
confidence: 99%
“…Few other studies have investigated effects of estrogen on allopaternal or paternal behavior in juvenile or adult males. In prairie voles, however, Cushing et al (2008) found that experimentally increasing the expression of estrogen receptor a (ERa) in the medial amygdala (MeA) via a viral vector inhibited parental behavior in adult males, while increasing ERa expression in the bed nucleus of the stria terminalis (BNST) had no effect (Lei et al 2010).…”
Section: Neuroendocrine Influences On Paternal Behaviormentioning
confidence: 99%